The first record of Dolops carvalhoi (Crustacea: Branchiura) parasitizing three farmed fish species of the Peruvian Amazon - Gonzales, Anai Flores; Babilonia, Jorge; Paredes, Marian; Delgado, Patrick Mathews [UNESP]; Oliveira, Marcos Sidney Brito; Fernández-Méndez, Christian (Springer Nature, 2024)
Branchiura are a crustacean parasite widely known around the world as fish lice. In South America, they have been most studied in Brazil as with high levels of infestation, the parasites can be harmful to the health of fish and cause economic losses in fish farms. The objective of the present study is to provide, for the first time, significant information about the parasitic indices, infestation sites, and morphology of Dolops carvalhoi, and to report the appearance of a new host in the Amazon region of Peru. A total of 24 specimens of Colossoma macropomum, Piaractus brachypomus, and Calophysus macropterus from fish farms were individually analyzed to identify the presence of the ectoparasites. The Branchiura collected from the body surfaces of the fish were separated according to sex, the parasitic indices were calculated, and the parasites were clarified in 90% lactic acid for taxonomic identification. They were also preserved in 2.5% glutaraldehyde, and dehydration and critical point procedures were applied by scanning electron microscopy to visualize the detailed structures. The taxa identified was D. carvalhoi, which had a prevalence of 64.7%, a mean intensity of 1.6, and a mean abundance of 1 parasite/fish in C. macropterus; a prevalence of 100%, a mean intensity, and mean abundance of 2.8 parasites/fish in P. brachypomus; and a prevalence of 100%, but a mean intensity and mean abundance of 15 parasites/fish in C. macropomum. The pectoral and dorsal fins and the urogenital opening had the highest occurrence of D. carvalhoi in the host. Dolops carvalhoi has sexual dimorphism, and we reported for the first time the infestation of this parasite in leather fish C. macropterus.
Keywords: Amazonia; Aquaculture activity; Catfish; Parasite; Serrasalmidae